RECTAL MISOPROST VS INTA MUSCULAR SYNTOCINON IN THE MANAGEMENT OF THIRD STAGE OF LABOUR - Patil, Amrutha S. (Journal of Biomedical and Pharmaceutical Research, 2017)
Postpartum haemorrhage is a single largest and leading cause of severe maternal morbidity and mortality, not only in developing countries, but also in developed countries.